2022
DOI: 10.1200/edbk_359154
|View full text |Cite
|
Sign up to set email alerts
|

Global Aging and Cancer: Advancing Care Through Innovation

Abstract: The oncology field, like many others, is digitalizing rapidly, a phenomenon that may have been accelerated by the COVID-19 pandemic. This movement is creating opportunities and challenges. Another rapidly developing change is the aging of the global population; because cancer is a disease of aging, there is a need for health systems to adapt to taking care of such patients. In this article, we address how these innovative technologies can be leveraged to improve the care of older patients with cancer beyond ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…This process also causes the removal of these damaged cells by activating the immune system through the SASP, but if the cells evade this fate, it may lead to tumorigenesis [ 34 ]. Emerging evidence showed that several ARGs may be the cause of onset and advancement of cancers due to regulation of the process of aging and cellular senescence by these ARGs and could be used as a target for cancer therapy [ 35 , 36 ]. Consequently, to analyze the exact role that aging plays in osteosarcoma, the transcriptome of the ARGs needs to be investigated thoroughly.…”
Section: Discussionmentioning
confidence: 99%
“…This process also causes the removal of these damaged cells by activating the immune system through the SASP, but if the cells evade this fate, it may lead to tumorigenesis [ 34 ]. Emerging evidence showed that several ARGs may be the cause of onset and advancement of cancers due to regulation of the process of aging and cellular senescence by these ARGs and could be used as a target for cancer therapy [ 35 , 36 ]. Consequently, to analyze the exact role that aging plays in osteosarcoma, the transcriptome of the ARGs needs to be investigated thoroughly.…”
Section: Discussionmentioning
confidence: 99%
“…Discussions about advantages and hazards, tailored to each woman's health situation, are essential for optimizing screening procedures [ 9 ]. Once cancer is a disease of aging, health systems need to adapt healthcare to such patients [ 19 ]. When treating BC in older women, it is vital to strike a balance between the treatment's curative purpose and the patient's comorbidities and quality of life [ 20 ] Patients in their later years have a decreased life expectancy and a different kind of longevity advantage.…”
Section: Introductionmentioning
confidence: 99%